Gut microbiota and risk of coronary heart disease: a two-sample Mendelian randomization study - Hu, Xiang-zhi; Fu, Ling-ling; Ye, Bin; Ao, Man; Yan, Ming; Feng, Hong-chao (Frontiers in Cardiovascular Medicine, 2024)
Background The relationship between gut microbiota composition and coronary heart disease (CHD) has been recently reported in several observational studies. However, the causal effect of gut microbiota on coronary heart disease is uncharted. Objective This study attempted to investigate the effect of gut microbiota on coronary heart disease by Mendelian randomization (MR) analysis. Methods Through the two-sample MR method, single-nucleotide polymorphisms relevant to gut microbiota were selected as instrument variables to evaluate the causal association between gut microbiota and the risk of CHD. Results According to the selection criteria of the inverse variance-weighted average method, Class Actinobacteria, Class Lentisphaeria, Family Clostridiales vadinBB60group, Genus Clostridium innocuum group, Genus Bifidobacterium, Genus Butyricicoccus, Genus Oxalobacter, Genus Turicibacter, and Order Victivallales, presented a suggestive association with coronary heart disease. Conclusion This two-sample Mendelian randomization study found that gut microbiota was causally associated with coronary heart disease. Further randomized controlled trials are needed to clarify the protective effect of probiotics on coronary heart disease and their specific protective mechanisms.